Navigating University: The Design and Evaluation of a Holistic Support Programme for Autistic Students in Higher Education - Charlotte Brownlow; Neil Martin; Donna-Marie Thompson; Amelia Dowe; Ding Abawi; Jessica Harrison; Sonja March (MDPI AG, 2023)
Successfully engaging with university study can be challenging for autistic students and has been highlighted in the research literature as an area of concern. This study sought to address support for autistic students at one Australian university through the development of a bespoke programme called A-Skills. The programme was co-designed with autistic students drawing on principles of self-determination theory and it aimed to develop study and student life skills. This paper presents a longitudinal evaluation of the programme using semi-structured interviews and user engagement metrics from the online platform. Our findings indicated that engagement with the programme varied between individuals but adopting a principle of co-design ensured that the topics of focus were important to the needs of the students it sought to support. Further, interview data suggested both positive sentiment and value towards the initiative amongst participants. Although online delivery enabled choice, there were potential challenges in fostering relatedness, which was addressed to some degree through synchronous online weekly sessions facilitated by an autistic student. Core to the success of A-Skills is the co-design approach as a central principle in the design, development and evaluation of the programme. With continued research and iterative design, the programme could be adopted more widely.